Test Automation Framework for Content Delivery Network - Yadav, Jayesh Kumar; GS, Nagaraja (International Journal of Computer Sciences and Engineering, 2021)
Content Delivery Network, or a CDN, is a globally distributed network of servers that helps provide good availability, faster and reliable performance, and security to the content distributors. In order to maintain a secure and reliable system any change proposed for the network needs to be thoroughly tested. But testing a full software release takes a lot of time because of a very huge database and complex dependencies between them. This increases the total time taken in the software development life cycle. In the existing system, a tester has to write test scripts for every Change Request (CR), which is a documented request to modify the current software system. This effort can be substantially reduced by developing a tool which can accurately test all the changes by dynamically generating test values for each metadata tag. (In this paper, the term “metadata tag” refers to settings used to control the configuration of web servers). This reduces the time to figure out all complex dependencies and test for each and every change made. The aim is to provide a simple, clean interface which allows the user to select a Change Request he wants to test and then dynamically generate positive and negative test values on which test will run on and provide a detailed result to the user whether the test passed or not.